SUBSTITUSI TEPUNG TAPIOKA DENGAN TEPUNG SAGU TERHADAP KUALITAS ORGANOLEPTIK NUGGET DAGING AYAM - Haumahu, Aldrin Sergio; Liur, Isye Jean; Tiven, Nafly Comilo (MARSEGU : Jurnal Sains dan Teknologi, 2026)
This research is to determine the effect of tapioca flour substitution with sago flour on the organoleptic quality of chicken nuggets and determine the optimal substitution percentage. The research used a Completely Randomized Design (CRD) with 5 substitution treatments, namely P0 (100% tapioca : 0% sago), P1 (75% tapioca : 25% sago), P2 (50% tapioca : 50% sago), P3 (25% tapioca : 75% sago), and P4 (0% tapioca : 100% sago). Each treatment was repeated 30 times using 30 untrained panelists. The parameters observed included color, aroma, texture, and taste using a hedonic test with a scale of 1-5. Data were analyzed using ANOVA and continued with Duncan's test at the 5% level. The results showed that sago flour substitution did not significantly affect color and taste (P>0.05), but had a very significant effect on aroma (P<0.01) and a significant effect on texture (P<0.05). Treatment P1 (25% sago flour substitution) gave the best results in texture (4.47) and taste (4.33), while P2 (50% sago flour substitution) produced the best aroma (4.50). 100% sago flour substitution (P4) caused a drastic decrease in aroma (3.90), texture (3.87), and taste (3.93). It was concluded that substitution of tapioca flour with sago flour of 25-50% is the optimal formulation to produce chicken nuggets with good organoleptic quality and is still accepted by consumers.